THE EFFECT OF ECONOMIC AND DEMOGRAPHIC CHARACTERISTICS ON UNEMPLOYMENT IN SOUTH SULAWESI - ZAINAL, MUHAMMAD FAHD (Jurnal Ilmiah Mahasiswa FEB, 2018)
Unemployment is one of major problems faced by all countries, includingdeveloped countries. This problem also occurs in all provinces in Indonesia, includingSouth Sulawesi. The unemployment rate in South Sulawesi is even higher than thenational level in 2017. The objective of this research is to analyze the effect ofeconomic and demographic characteristics on unemployment in South Sulawesi in2017. While economic characteristics includes Gross Regional Domestic Product(GRDP) and city’s minimum wage, demographic characteristics consists of gender,age, status in household, marital status, and education. The data of this research wasobtained from the Central Statistics Agency of South Sulawesi and the result of 2017national survey on labor force (SAKERNAS) and was analyzed using logisticregression analysis processed in Stata 14.2. The result shows that variables withtendencies to influence a person to become unemployed in South Sulawesi are GRDP,gender, age, status in household, marital status, and education, in this case senior highschool and university graduates are affected. Furthermore, variables that do not haveany significant effect on unemployment in South Sulawesi are the city’s minimumwage and education, in this case elementary school and junior high school graduatesare not affected.Keywords: unemployment, economic characteristics, demographic characteristics,South Sulawesi